KAP Study on OTC Drugs and Drugs Abuse Among Community - Kumawat, Bhagat Amruta Baban; Patil Shreeyash Jaywant; Shinde Priya; Junghare Kiran; Patil Sheetal; Deshmukh Sampada; Sapkal Akanksha; Pawar Pranav (Asian Journal of Pharmaceutical Research and Development, 2026)
This study, titled “KAP Study on OTC Drugs and OTC Drug Abuse Among Community,” aimed to assess the knowledge, attitudes, and practices regarding the use and misuse of over-the-counter (OTC) drugs among 200 community participants using a structured questionnaire. The findings showed that although many participants understood that OTC drugs can be purchased without a prescription, awareness about their risks and adverse effects was limited. Unsafe practices such as self-medication and improper use were observed, with easy availability and lack of awareness contributing to misuse. The study emphasizes the need for public awareness, stronger regulations, and greater involvement of healthcare professionals to promote safe and rational use of OTC medications.